Breaking paradigms in the treatment of psoriasis: Use of botulinum toxin for the treatment of plaque psoriasis. Issue 6 (8th October 2020) - González, Cesar; Franco, Manuel; Londoño, Angela; Valenzuela, Fernando
Abstract: Some studies have demonstrated that neurotransmitters are involved in the pathogenesis of numerous skin conditions, including psoriasis, addressing the close correlation between the skin and the central nervous system. There are reports showing psoriasis improvement after peripheral nervous system injury. In addition, botulinum toxin has been reported as a treatment for several diseases, including psoriasis. This is a proof‐of‐concept study of botulinum toxin and psoriasis, involving eight patients with stable and recalcitrant plaques of psoriasis vulgaris. The lesions were 5 cm 2 at the maximum. Botulinum toxin Dysport (Ipsen Biopharm, Wrexham, UK), 5 units per cm 2, was administered in one subcutaneous application. Patients were then evaluated at 2 and 4 weeks after treatment. Our results indicated a substantial improvement in all patients, 4 weeks after treatment, with no significant side effects. Our preliminary conclusion is that botulinum toxin represents a novel mechanism for interfering with the immunopathogenesis of psoriasis and improving the quality of life of our patients.